Principles of Financial Regulation : A Dynamic Portfolio Approach - Stiglitz, Joseph E. (Washington, DC: World Bank, 2014)
Economists seeking explanations for the global financial crisis of 1997-99 are reaching consensus that a major factor was weak financial institutions, which resulted in part from inadequate government regulations. At the same time many developing countries are struggling with an overregulated financial system-one that stifles innovation and the flow of credit to new entrepreneurs and that can stunt the growth of well-established firms. In particular, too many countries are relying excessively on capital adequacy standards, which are inefficient and sometimes counterproductive. The author argues that financial systems can be reformed successfully using a 'dynamic portfolio approach' aimed at managing the incentives and constraints that affect not only financial institutions exposure to risk but also their ability to cope with it. The article sets out general principles of financial regulation and shows how the dynamic portfolio approach can help countries deal with the special problems that arise during the transition to a more liberalized economy as well as those that arise in dealing with a financial crisis similar to the 1997 crisis in East Asia.